2019
DOI: 10.1111/cpr.12732
|View full text |Cite
|
Sign up to set email alerts
|

Gamabufotalin induces a negative feedback loop connecting ATP1A3 expression and the AQP4 pathway to promote temozolomide sensitivity in glioblastoma cells by targeting the amino acid Thr794

Abstract: Objectives: Temozolomide (TMZ) is one of the most commonly used clinical drugs for glioblastoma (GBM) treatment, but its drug sensitivity needs to be improved.Gamabufotalin (CS-6), the primary component of the traditional Chinese medicine "ChanSu," was shown to have strong anti-cancer activity. However, more efforts should be directed towards reducing its toxicity or effective treatment doses.Methods: Target fishing experiment, Western blotting, PCR, confocal immunofluorescence and molecular cloning techniques… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 38 publications
(72 reference statements)
3
13
0
Order By: Relevance
“…2015; Zou et al, 2020;Lan et al, 2020). Nevertheless, precise mechanisms have yet to be fully elucidated.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…2015; Zou et al, 2020;Lan et al, 2020). Nevertheless, precise mechanisms have yet to be fully elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…Recent evidence suggests that AQP4 expression may be linked to several diseases such as cancer ( Papadopoulos and Saadoun, 2015 ; Zou et al, 2020 ; Lan et al, 2020 ). Nevertheless, precise mechanisms have yet to be fully elucidated.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been reported that bufalin inhibits the growth of hepatocellular carcinoma (HCC) cells, which is correlated with the expression level of ATP1A3 in HCC cells ( 39 ). Another study reported that activation of ATP1A3 could sensitize glioblastoma cells to temozolomide ( 41 ). However, the role of PCRGs in the development of ccRCC has not been reported, and further research is needed.…”
Section: Discussionmentioning
confidence: 99%